Connecting to Compete 2010 : Trade Logistics in the Global Economy--The Logistics Performance Index and Its Indicators - Arvis, Jean-Francois; Alina Mustra, Monica; Ojala, Lauri; Shepherd, Ben; Saslavsky, Daniel (World Bank, Washington, DC, 2016)
This report presents the findings of the second edition of Connecting to Compete, a report on the new dataset for the 2010 Logistics Performance Index (LPI) and its component indicators. Based on a worldwide survey of global freight forwarders and express carriers, the LPI is a benchmarking tool developed by the World Bank that measures performance along the logistics supply chain within a country. The index can help countries identify challenges and opportunities and improve their logistics performance. The World Bank conducts the survey every two years. The 2010 LPI also provides a snapshot of selected performance indicators in nearly 130 countries, including expanded information on the time, cost, and reliability of import and export supply chains, infrastructure quality, performance of core services, and the friendliness of trade clearance procedures. The 2010 LPI and its indicators encapsulate the firsthand knowledge of movers of international trade, collected amid the economic turmoil of 2009. This information is relevant for policymakers and the private sector seeking to identify priorities for reform agendas. Findings include the following. First, except in high-income countries, the availability and quality of trade-related infrastructure is a major constraint to performance, but the specific priorities tend to vary across countries. Second, efficient border management and coordination of the various agencies involved in border clearance is increasingly important. Third, a major challenge for the international community is how to help the lowest performing countries benefit from an increasingly open global trading system.